2017
DOI: 10.18632/oncotarget.21791
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA XIST promotes cell growth and metastasis through regulating miR-139-5p mediated Wnt/β-catenin signaling pathway in bladder cancer

Abstract: Bladder cancer is one of the most common urological malignancy all over the world. Recently, long non-coding RNA (lncRNA) XIST has been identified as an oncogenic gene in several type of cancers. However, the expression level and functional role of XIST in bladder cancer remain largely unknown. In the present study, we found that XIST was significantly up-regulated in bladder cancer tissues and cell lines, and was correlated with poor prognosis of bladder cancer patients. Furthermore, XIST knockdown significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 45 publications
3
77
0
Order By: Relevance
“…Numerous studies have suggested the importance of Wnt-b-catenin signaling in several cancers (44). Furthermore, Wnt-b-catenin has been shown to play important roles during epithelial-mesenchymal transition (45), cell proliferation and metastasis (24), and drag resistance (46) in bladder cancer. In the present study, RBM5 knockdown activated the Wnt-b-catenin pathway by promoting the expression of b-catenin and cyclin D1 while decreasing the apoptosis marker caspase-3 at the protein level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested the importance of Wnt-b-catenin signaling in several cancers (44). Furthermore, Wnt-b-catenin has been shown to play important roles during epithelial-mesenchymal transition (45), cell proliferation and metastasis (24), and drag resistance (46) in bladder cancer. In the present study, RBM5 knockdown activated the Wnt-b-catenin pathway by promoting the expression of b-catenin and cyclin D1 while decreasing the apoptosis marker caspase-3 at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play a critical role in tumor progression by regulating gene expression at the posttranscriptional level. Several miRNAs, including miR-22 (20), miR-21 (21), miR-429 (22), miR-34a (23), and miR-139-5p (24), have been implicated in bladder cancer. miR-432-5p has been reported to play an important role in tumor progression.…”
mentioning
confidence: 99%
“…More and more studies have confirmed that lncRNAs could regulate the malignant behaviours of tumour cells through its regulation of gene expression and functions . For instance, in bladder cancer, Hu et al reported that XIST promotes cell growth and metastasis through regulating miR‐139‐5p mediated Wnt/β‐catenin signalling pathway in bladder cancer . LncRNA UCA1 Promotes mitochondrial function of bladder cancer via the miR‐195/ARL2 signalling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned, Wnt/β-catenin signaling was involved in TGFβ1-mediated fibrosis, and miR-139 could target to inhibit several crucial factors in Wnt signaling pathway, such as CTNNB1, FZD4 (Long et al, 2017), TCF-4 (Gu et al, 2014), and Wnt1 (Hu et al, 2017). Apart from these factors, Kaiso/CTNND1 complex has been regarded as a modulator of the canonical Wnt/β-catenin signaling pathway (Kantidze, Kamalyukova, & Razin, 2009).…”
Section: Smad2/3/4 Complex Inhibits the Transcription Of Mir-139 Bymentioning
confidence: 99%
“…Under TGFβ1 stimulation, miRNA‐200b stimulates the proliferation of HTFs by targeting p27/kip1 and RND3 (Tong et al, ). More important, miR‐139 has been reported to regulate several crucial factors in Wnt signaling, including CTNNB1, FZD4 (Long et al, ), TCF‐4 (Gu, Li, & Wang, ), and Wnt1 (Hu et al, ), which inspired us to speculate that miR‐139 may participate in TGFβ1‐mediated HTF activation and proliferation through Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%